Solubilization of tumour-specific antigen from plasma membrane of an aminoazo-dye-induced rat hepatoma - Baldwin, R. W. (1972)
Plasma membrane fractions isolated from cells of an aminoazo-dye-induced rat hepatoma were solubilized by limited papain digestion. DEAE-cellulose chromatography yielded a discrete component retaining tumour-specific antigen as measured by its capacity to neutralize antibody in tumour-immune sera, which reacts in immunofluorescence tests with the plasma membrane of intact hepatoma cells. Solubilized plasma membrane fractions also elicited a tumour-specific humoral antibody response in syngeneic rats. The relative inefficiency of antigen isolation procedures would seem to preclude the use of solubilized antigen for immunotherapy, but these preparations are important in studying the nature of tumour antigen expression during chemical carcinogenesis and for analysing the involvement of antigen–antibody complexes in tumour immunity.